A multilevel path analysis of social networks and social interaction in the neighbourhood - van den Berg, Pauline; Timmermans, Harry (REGION, 2015)
The topic of neighbourhood-based social interactions has gained attention in the last decades in the light of urban policies that aim to deal with problems regarding social segregation and exclusion, quality of life and liveability in urban areas. Social interactions are expected to play an important role in dealing with these problems. However, empirical studies investigating to which extent neighbourhood characteristics can improve social contacts among residents are scarce and inconclusive. Therefore, this paper studies the role of socio-demographics and neighbourhood characteristics in the formation of social network ties and social interactions with neighbours. Based on data collected in 2011 in 70 different neighbourhoods of Eindhoven in the Netherlands in a survey among 751 respondents these relationships are analysed using a multi-level path analysis approach. The results indicate that neighbourhood-based contacts are influenced by personal and household characteristics, such as education, income, work status, ethnicity, household composition, and years at the current address. Neighbourhood characteristics are not found to affect social network size, the share of neighbours in the network or the frequency of interaction with neighbours.